Fully quantum state-resolved inelastic scattering of NO(X) + Kr: differential cross sections and product rotational alignment. - Brouard, M; Chadwick, H; Gordon, S; Hornung, B; Nichols, B; Kłos, J; Aoiz, F; Stolte, S (American Institute of Physics, 2014)
Fully quantum state selected and resolved inelastic scattering of NO(X) by krypton has been investigated. Initial Λ-doublet state selection is achieved using an inhomogeneous hexapole electric field. Differential cross sections and even-moment polarization dependent differential cross sections have been obtained at a collision energy of 514 cm^−1 for both spin-orbit and parity conserving and changing collisions. Experimental results are compared with those obtained from quantum scattering calculations and are shown to be in very good agreement. Hard shell quantum scattering calculations are also performed to determine the effects of the different parts of the potential on the scattering dynamics. Comparisons are also made with the NO(X)+Ar system.